Analisis Determinan Efisiensi Bank Umum Syariah Indonesia Dengan Variabel Moderating Profitabilitas - Ranaswijaya, Ranaswijaya; Kristin, Ari; Muhlis, Muhlis (MALIA: Journal of Islamic Banking and Finance, 2019)
The purpose of this study is to examine the effect of Non Performing Financing (NPF) and Bank Size on the profitability and efficiency level of Islamic Commercial Banks, as well as the effect of profitability if it moderates the effect of Non Performing Financing (NPF) and Bank Size on the level of efficiency of Islamic Commercial Banks. The level of efficiency is obtained through efficiency analysis with Data Envelopment Analysis (DEA), The variables of input output consist of tabungan iB, giro iB, and deposito iB, while output consist of murabahah financing, mudharabah financing, musyarakah financing,and investment in securities. Data used during the period 2014-2017 which includes 13 Islamic Commercial Banks. The results of the study indicate that Bank Victoria Syariah achieved optimal efficiency values and the lowest efficiency of Bank Syariah Bukopin. The results of the hypothesis indicate that Non Performing Financing (NPF) has a significant negative effect on profitability and the level of efficiency of Islamic commercial banks. Bank size has no significant positive effect on profitability and has no significant negative effect on the efficiency of Islamic commercial banks. Profitability has no significant positive effect on the level of efficiency, and is not able to significantly moderate the influence of NPF and bank size on the level of efficiency of Islamic commercial banks.